2009
DOI: 10.1071/rdv21n1ab145
|View full text |Cite
|
Sign up to set email alerts
|

145 Factors Affecting Pregnancy Rate Following Timed Embryo Transfer Program in Cattle Under Field Conditions

Abstract: Hormonal estrus synchronization followed by heat detection of recipient animals is a widely used technique in embryo transfer (ET) programs around the world. However, the successful outcomes of ET rely heavily on appropriate heat detection of recipient animals. Additionally, limited availability of personnel and time to detect heat makes ET impractical at times. Therefore, pregnancy rates (PR) following a timed embryo transfer (TET) program were evaluated taking into account different variables of recipient co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The side of transfer (right or left) was recorded. Diameter of CL and type of CL (Purcell, Beal, & Gray, ; Scenna et al, ; Spell, Beal, Corah, & Lamb, ) were defined (Corpus luteum type: CLa = asymmetric, non‐embedded in ovary and soft texture, CLb = non‐embedded in ovarium, classic mushroom‐like and with cavity and CLc: prominent papillae, embedded in the ovary and compact texture). During the embryo transfer, three groups were formed according to cervix transfer score: easy (<60 s), moderate (60–80 s) and difficulty (>80 s).…”
Section: Methodsmentioning
confidence: 99%
“…The side of transfer (right or left) was recorded. Diameter of CL and type of CL (Purcell, Beal, & Gray, ; Scenna et al, ; Spell, Beal, Corah, & Lamb, ) were defined (Corpus luteum type: CLa = asymmetric, non‐embedded in ovary and soft texture, CLb = non‐embedded in ovarium, classic mushroom‐like and with cavity and CLc: prominent papillae, embedded in the ovary and compact texture). During the embryo transfer, three groups were formed according to cervix transfer score: easy (<60 s), moderate (60–80 s) and difficulty (>80 s).…”
Section: Methodsmentioning
confidence: 99%
“…[15][16][17] These two groups of practitioners and scientists described the criteria that are, for the most part, still used today as a general guideline for embryo evaluation and prediction of potential pregnancy. The latest of those papers 17 described numerous parameters commonly used for embryo evaluation, including stage of embryonic development and structural features such as embryo size and shape, presence of extruded cells or degenerated cells, color characteristic, number and compactness of the cells (also called blastomeres) that comprise the early embryo, integrity of the zona pellucida, and presence or absence of vacuoles within the cytoplasm of the embryonic blastomeres.…”
Section: Refinement Of the Morphological Embryo Evaluation Methodsmentioning
confidence: 99%
“…Quality grade 1 and 2 embryos typically yield higher pregnancy rates than quality grade 3. One study 24 showed no difference in pregnancy rate among cows receiving grade 1 or 2 embryos (74.1% and 71.8%, respectively), whereas another study 16 showed that quality grade 1 embryos had a greater probability to conceive (odds ratio 1.62) compared with quality grade 2 or 3 embryos. Conception rate of quality grade 1 embryos was reported as 76% for fresh embryos and 64% for frozen embryos.…”
Section: The Effectiveness Of Morphological Embryo Evaluationmentioning
confidence: 99%